Trophic ecology of Pomatoschistus microps within an intertidal bay (Roscoff, France), investigated through gut content and stable isotope analyses. (25th June 2013) - Leclerc, Jean‐Charles; Riera, Pascal; Noël, Laure M.‐L. J.; Leroux, Cédric; Andersen, Ann C.
Abstract The diet of Pomatoschistus microps has been studied using both gut content and stable isotope analyses. In the Roscoff Aber Bay (Brittany, France), this fish is commonly found on sandy muddy intertidal flats. Gut content analyses were also interpreted using trophic indices. Owing to the large diversity of prey consumed, these indices emphasised the opportunistic feeding behaviour of P. microps. Here, this species fed mainly on endofauna with meiofauna being of high relative importance. The main biotic components of its trophic habitat, characterized by δ13C and δ15N, provided evidence of a major trophic pathway based on drift Enteromorpha sp. Trophic positions estimated by both diet analyses and isotopic analyses led to similar results. In this bay, P. microps is a first‐order predator with a low degree of omnivory. Despite a preferential consumption of the amphipod Corophium arenarium, we assumed that this goby behaves as a generalist feeding on a uniform variety of endofauna taxa.